Renegotiation-proof contracts with moral hazard and persistent private information - Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2011)
How does renegotiation affect contracts between a principal and an agent subject to persistent private information and moral hazard? This paper introduces a concept of renegotiation-proofness, which adapts to stochastic games the concepts of weak renegotiation-proofness and internal consistency by exploiting natural comparisons across states. When the agent has exponential utility and cost of effort, each separating renegotiation-proof contract is characterized by a single sensitivity parameter, which determines how the agent's promised utility varies with reported cash flows. The optimal contract among those always causes immiserization. Reducing the agent's cost of effort can harm the principal by increasing the tension between moral hazard and reporting problems. Truthfulness of the constructed contracts is obtained by allowing jumps in cash flow reports and turning the agent's reporting problem into an impulse control problem. This approach shows that self-correcting reports are optimal off the equilibrium path. The paper also discusses the case of partially pooling contracts and of permanent outside options for the agent, illustrating the interaction between cash flow persistence, renegotiation, moral hazard, and information revelation.
Keywords: D82; D86; C73; G30; 330; Repeated Agency; Asymmetric Information; Persistent Information; Contract Theory; Principal Agent; Limited Commitment; Renegotiation; Recursive Contracts